Fatores que influenciam no comprometimento dos trabalhadores para com os objetivos institucionais. Estudo de caso em uma instituição pública - Costa, Valeria Bellas da (2003)
This work intends to elaborate proposais, within Human Resources Service, to maximization institutional commitment, presenting the result of a research about the connection between Satisfaction, Commitment and Interna! Ambience. For such was used a research approach supported by bibliographical research, identification of other similar researches and on a case study carried out at of Institutional Development and Management Coordination (CDIGIENSP/FIOCRUZ). For the case study were applied questionnaires structured to evaluate of organizational ambience. In the end are presented conclusions about conditions related to satisfaction possibilities and workers commitment with órganizational goals.